Pediatric polysomnography-flagging etiologies and impact on the clinical timeline - Rani, Seema; Schanz, John; Chauhan, Kapil; Kolb, August; Gatta, Victoria; Strang, Abigail; Chidekel, Aaron C. (Frontiers in Sleep, 2024)
Background/objective There is a paucity of literature regarding “flagging” abnormal sleep studies for expedited review. This single-center retrospective analysis (n = 266) of flagged polysomnography studies from 2019 to 2022 aimed to investigate flagging and its impact on the clinical timeline. Methods Two hundred sixty-six flagged polysomnography studies from 2019 to 2022 were retrospectively reviewed. Results Flagged study etiologies included repetitive brief oxygen desaturations (46.6%), sustained desaturations (32.3%), sustained hypercapnia (5.6%), or other concerning events (15.5%). The median time between a flagged study and scoring report finalization, medical intervention, and surgical intervention were 0 (2) days, 2 (3) days, 5 (11.25) days, and 44 (73) days, respectively. Patients with apnea–hypopnea index >30 had less time between a flagged study and surgical intervention (65.3 ± 96.7 days vs. 112 ± 119 days, p = 0.044). Conclusion As anticipated, the time to surgical intervention was longer than to medical intervention. Patients with a higher disease severity experienced quicker scoring, report finalization, and surgical intervention.